The Efficacy and Safety of Trabeculectomy after Failed Primary Glaucoma Drainage Devices - Daniel Wang; Zhuangjun Si; Sanjay G. Asrani; Joanne C. Wen; Divakar Gupta (Ophthalmology and Therapy)
Abstract Introduction Trabeculectomy is not usually considered for uncontrolled intraocular pressure (IOP) after glaucoma drainage devices (GDD) because of concern that the conjunctiva has been violated and future trabeculectomy surgery is likely to fail due to fibrosis. We examined the clinical outcomes of patients who underwent a trabeculectomy after failed primary GDD. Methods This is a cross-sectional study of all patients who had a glaucoma drainage implant that failed or was inadequate in lowering IOP and underwent a trabeculectomy in the same eye from January 2016 to December 2022. Results A total of 23 eyes in 22 patients met our criteria. Average IOP [± standard deviation (SD)] prior to trabeculectomy was 21.7 ± 9.3 on 3.2 ± 1.3 medications. The length of follow-up was between 0.3 and 5.0 years with an average follow-up time of 2.2 years. At 1 year (n = 16), IOP was 11 ± 1.9 mm Hg on 1.8 ± 1.5 medications. At 2 years, the average IOP was 11.8 ± 4.6 on 1.9 ± 1.4 medications. At all follow-up points, the decrease in IOP and medication was statistically significant compared with baseline (paired t-tests; p < 0.05). Most postoperative complications self-resolved with medical management (three early wound leaks, two late wound leaks, two instances of hypotony maculopathy, and one instance of cystoid macular edema). One early wound leak required surgical repair. One eye underwent an additional GDD surgery, and three eyes underwent bleb needling. In all, 20 (87%) eyes at final visit were within two lines of their baseline vision prior to trabeculectomy. No eyes progressed to having no light perception visual acuity or had an ocular infection. Conclusions This study suggests that trabeculectomy after a GDD is an effective and safe option for IOP control and glaucoma medication reduction. In this small sample of surgical cases, complication and reoperation rates were comparable to published rates.